Aspects of Common Eider Nesting Ecology in Labrador - Chaulk, Keith; Robertson, Gregory J.; Montevecchi, William A.; Ryan, Pierre C. (ARCTIC, 2010)
The status, distribution, and nesting ecology of common eiders (Somateria mollissima) breeding in Labrador are not well known. This study is an initial effort to improve understanding of the nesting ecology of eiders on the Labrador coast, a zone of intergradation between the northern (S. m. borealis) and American (S. m. dresseri) subspecies of common eider. During 1998 and 1999, 187 islands were surveyed for nesting eiders at four sites (from north to south: Nain, Hopedale, Makkovik, St. Peter’s Bay) along 750 km of the coast. Nest initiation dates (calculated by candling eggs) ranged over a four- to five-week period and were positively associated with latitude: the earliest mean initiation date (5 June) was in St. Peter’s Bay in the south and the latest (27 June) at Nain in the north. Mean clutch size ranged from 3.5 to 4.2 and varied by area and year; eiders nesting in Nain had the smallest clutches. In 1999, the highest nest density (49.8 nests/ha) was observed in Nain and the lowest (3.9 nests/ha) in Makkovik. In some cases, we used boat surveys to assess eider presence and absence and found it to be a reliable method; this search technique could be beneficial to researchers working in remote locations where operational costs are high. On connaît mal le statut, la distribution et l’écologie de nidification de l’eider à duvet (Somateria mollissima) qui se reproduit au Labrador. Cette étude représente un premier pas vers une meilleure compréhension de l’écologie de nidification de l’eider sur la côte du Labrador, une zone de chevauchement entre la sous-espèce du nord (S. m. borealis) et celle américaine (S. m. dresseri) de l’eider à duvet. Durant 1998 et 1999, on a cherché des eiders nicheurs dans 187 îlots à quatre endroits (du nord au sud: Nain, Hopedale, Makkovik, baie de St. Peter’s) répartis sur 750 km de rivage. Les dates du début de la couvaison (calculées en mirant les oeufs) s’étalaient sur une période de quatre à cinq semaines et étaient associées positivement à la latitude: c’est dans la baie de ...